Peripheral polyneuropathy after bariatric surgery for morbid obesity - I-Ching Lin; Ying Li Lin (Wolters Kluwer Medknow Publications, 2011)
A patient with peripheral polyneuropathy after bariatric surgery for morbid obesity is reported. She suffered from frequent episodes of vomiting and abdominal pain after surgery. Muscle weakness in her lower limbs developed 5 months later and she experienced difficulty in walking and standing. Wrist drop, foot drop, and marked distal limb muscle atrophy were found bilaterally. Electromyography showed the presence of sensorimotor axonal polyneuropathy. Nutritional deficiencies may play an important role in pathogenesis. This uncommon neurological complication might be due to rapid weight loss and vitamin deficiency. Physicians who take care for patients after bariatric surgery should have a high index of awareness for the neurologic complications, and routine vitamin supplementation might be useful for these patients.